To develop an application in android for smart phones tasks processing to the cloud to detect malware in application and generate reports - Mahajan, Sangita; Sangle, Suvarna; Khairnar, Gayatri (International Journal of Computer Sciences and Engineering, 2025)
Most of us use android phones these days and also uses the multiple applications and facilities frequently. Play store provides great number of application but unfortunately few of those applications are fraud. Such applications dose damage to phone and also possibly data thefts. Hence such applications must be marked, so that they will be recognizable for play store users. So we are proposing a web application which will process the information, comments and the reviews of the application on cloud server. As we are handling the big data here so the process is done on cloud server and malware is detected. So it will be easier to decide which application is fraud or not. Multiple applications can be processed at a time with the web application.